A WTS Power Conversion Stage With Multilevel Converters Operating in the Medium Voltage Range - Verne, Santiago Andres (2012)
A high power medium voltage converter for wind turbine system is presented in this paper. The proposal mitigates classic design tradeoffs around low voltage, high current link between the generator and the utility grid on the megawatt range. The power converter is based on Multilevel Converters technology which allows to extend the power-handling capability of the electronic switches, reaching the medium voltage operation without step-up transformers. The converter controllers are based on the Finite-States Model Predictive Control approach, leading to fast dynamic response and DC bus voltages equalization. The performance of the control scheme is evaluated with computer simulations.